Validation of a survey tool for use in cross-cultural studies - Costa FA; Duggan C; Bates I (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
There is a need for tools to measure the information patients need in order for healthcare professionals in general, and particularly pharmacists, to communicate effectively and play an active part in the way patients manage their medicines. Previous research has developed and validated constructs to measure patients' desires for information and their perceptions of how useful their medicines are. It is important to develop these tools for use in different settings and countries so that best practice is shared and is based on the best available evidence. Objectives: this project sought to validate of a survey tool measuring the "Extent of Information Desired" (EID), the "Perceived Utility of Medicines" (PUM), and the "Anxiety about Illness" (AI) that had been previously translated for use with Portuguese patients. Methods: The scales were validated in a patient sample of 596: construct validity was explored in Factor analysis (PCA) and internal consistency analysed using Cronbach's alpha. Criterion validity was explored correlating scores to the AI scale and patients' perceived health status. Discriminatory power was assessed using ANOVA. Temporal stability was explored in a sub-sample of patients who responded at two time points, using a T-test to compare their mean scores. Results: Construct validity results indicated the need to remove 1 item from the Perceived Harm of Medicines (PHM) and Perceived Benefit of Medicines (PBM) for use in a Portuguese sample and the abandon of the tolerance scale. The internal consistency was high for the EID, PBM and AI scales (alpha>0.600) and acceptable for the PHM scale (alpha=0.536). All scales, except the EID, were consistent over time (p>0.05; p<0.01). All the scales tested showed good discriminatory power. The comparison of the AI scale with the SF-36 indicated good criterion validity (p<0.05).Conclusion: The translated tool was valid and reliable in Portuguese patients- excluding the Tolerance scale. Some of the scales may benefit from further refinement, such as the PHM subscale.